2023
DOI: 10.1002/eem2.12620
|View full text |Cite
|
Sign up to set email alerts
|

Improved Efficiency and Stability of Organic Solar Cells by Interface Modification Using Atomic Layer Deposition of Ultrathin Aluminum Oxide

Abstract: The interfacial contacts between the electron transporting layers (ETLs) and the photoactive layers are crucial to device performance and stability for OSCs with inverted architecture. Herein, atomic layer deposition (ALD) fabricated ultrathin Al2O3 layers are applied to modify the ETLs/active blends (PM6:BTP‐BO‐4F) interfaces of OSCs, thus improving device performance. The ALD‐Al2O3 thin layers on ZnO significantly improved its surface morphology, which led to the decreased work function of ZnO and reduced re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…These formed hydroxyl radicals chemically react with and decompose the organic NFA molecules, as demonstrated by the well-known ITIC NFA system . Several routes have been shown to mitigate this effect, for example via C 60 self-assembled monolayers or via different surface treatments that passivate the surface defects leading to the hydroxyl radical-mediated degradation mechanisms. While some of these methods have presented good stability, they appear as challenging to scale up due to a lack of compatibility with roll-to-roll-based techniques, and thus alternative solutions must be explored. Another approach to limiting the photocatalytic degradation of NFA molecules by metal oxide ETLs is replacing TiO x and ZnO ETLs with other metal oxides that do not have a strong photocatalytic activity, e.g., SnO 2 …”
Section: Introductionmentioning
confidence: 99%
“…These formed hydroxyl radicals chemically react with and decompose the organic NFA molecules, as demonstrated by the well-known ITIC NFA system . Several routes have been shown to mitigate this effect, for example via C 60 self-assembled monolayers or via different surface treatments that passivate the surface defects leading to the hydroxyl radical-mediated degradation mechanisms. While some of these methods have presented good stability, they appear as challenging to scale up due to a lack of compatibility with roll-to-roll-based techniques, and thus alternative solutions must be explored. Another approach to limiting the photocatalytic degradation of NFA molecules by metal oxide ETLs is replacing TiO x and ZnO ETLs with other metal oxides that do not have a strong photocatalytic activity, e.g., SnO 2 …”
Section: Introductionmentioning
confidence: 99%
“…20,21 Nevertheless, ZnO has intrinsic limitation that it can be trapped in the ''light-soaking'' problem and thereby produce reactive free radicals upon exposure to ultraviolet light, resulting in the decomposition of photovoltaic materials. [22][23][24][25][26] Meanwhile, the unbalanced stoichiometric proportion of zinc and oxygen atoms during the formation of the ZnO film inevitably generates oxygen vacancies (VO + ) and zinc interstitial (Zni + ) defects. 27,28 These defects not only act as recombination centres to capture photogenerated carriers, but also absorb environmental oxygen and water, which seriously impair the electrical conductivity and lifetime of i-OSCs.…”
Section: Introductionmentioning
confidence: 99%
“…These reactions lead to the formation of hydroxyl radicals, which can cause decomposition of the organic molecules . While there has been several strategies to passivate such surface defects or suppress the photocatalytic activity of NFAs on ZnO to improve photostability, a more elegant and also practical approach is to overcome this degradation by developing metal oxide ETLs that possess lower photocatalytic activity, such as SnO 2 . In this context, we have recently shown that tuning the surface oxygen content in sputter-deposited TiO x ETLs enhances the long-term stability of PBDB-T:ITIC-based OPV devices significantly, when compared to conventional solution-processed metal oxide ETLs, due to reduced photocatalytic decomposition of the NFA molecule ITIC at the metal oxide ETL .…”
Section: Introductionmentioning
confidence: 99%